Management of Equine Metabolic Syndrome. (2nd November 2019) - Bowen, Mark
Abstract : Mark Bowen BVetMed MMedSci PhD DipACVIM DipECEIM DipECVSMR PFHEA FRCVS discusses this increasingly common and pressing equine welfare challenge